Unlocking the wordhord : Anglo-Saxon studies in memory of Edward B. Irving, Jr. - O'Brien O'Keeffe, Katherine, 1948-; Irving, Edward Burroughs, 1923-; Amodio, Mark (University of Toronto Press, 2003)
The Anglo-Saxons placed a great deal of importance on wisdom and learning, something Beowulf makes dramatically clear when he uses his 'wordhord' to command respect and admiration from his friends and foes alike. Modern day scholars no longer have recourse to the living language and culture of the Anglo-Saxons, and as a result must turn to their 'wordhords' - the literary, historical, and cultural artefacts that have survived in various degrees of intactness - to learn about life in Anglo-Saxon England. This collection of essays, gathered to honour the memory of the noted Anglo-Saxonist Edward B. Irving, Jr., brings together an international group of leading scholars who take the measure of Anglo-Saxon literary, textual, and lexical studies in the present moment. Ranging from philological and structural studies to ones that explicitly engage a variety of contemporary theoretical issues, they reflect the rich diversity of approaches to be found among Anglo-Saxonists. Subjects addressed include comparative work on Old English and Latin, and on Old English, ancient Greek, and South Slavic, notions of authorship and textual integrity, techniques of editing, heroic poetry, religious verse, lexicography, oral tradition, and material textuality. Offering a fresh reading of some popular pieces and inviting attention to some less-familiar texts, these previously unpublished essays illustrate the latest state of particular techniques for literary / critical analysis, textual recovery, and lexical studies.